2011
DOI: 10.1007/s10900-011-9469-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Near Real-Time Morbidity Data to Identify Heat-Related Illness Prevention Strategies in North Carolina

Abstract: Timely public health interventions reduce heat-related illnesses (HRIs). HRI emergency department (ED) visit data provide near real-time morbidity information to local and state public health practitioners and may be useful in directing HRI prevention efforts. This study examined statewide HRI ED visits in North Carolina (NC) from 2008-2010 by age group, month, ED disposition, chief complaint, and triage notes. The mean number of HRI ED visits per day was compared to the maximum daily temperature. The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 8 publications
6
30
0
Order By: Relevance
“…In North Carolina, many of the ED visits seen during the July event were likely work-related, as most occupations with high exposure to extreme heat employ individuals in these age categories [33]. Indeed, about onethird of all HRI visits in the NC DETECT dataset from 2008 to 2010 were work-related according to available triage notes [17]. One occupational group that is particularly vulnerable in North Carolina is migrant and seasonal farm workers, who exhibit the highest mortality rates for HRI of all farm workers across the U.S. [34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In North Carolina, many of the ED visits seen during the July event were likely work-related, as most occupations with high exposure to extreme heat employ individuals in these age categories [33]. Indeed, about onethird of all HRI visits in the NC DETECT dataset from 2008 to 2010 were work-related according to available triage notes [17]. One occupational group that is particularly vulnerable in North Carolina is migrant and seasonal farm workers, who exhibit the highest mortality rates for HRI of all farm workers across the U.S. [34].…”
Section: Discussionmentioning
confidence: 99%
“…Examination of available triage notes in the NC DETECT dataset revealed that [40 % of HRI visits were associated with exercise or recreation, of which two-thirds were linked to organized sports among 10-18 year olds [17]. Football players are particularly vulnerable to HRI due to uniform requirements and physiological characteristics that increase metabolic heat production and storage [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations